PROSPEK PENGEMBANGAN MINAPOLITAN DI KABUPATEN SITUBONDO - Yuli Wibowo; Nidya Shara Mahardika; Lia Sumi Karmila (JURNAL AGROTEKNOLOGI, 2020)
The Government of Situbondo Regency has implemented an agropolitan program in its region since 2013 to develop the potential of fisheries and marine resources. However, the program has not been able to develop as expected and still lacks the impact. This study aimed to determine the prospects for the development of the Minapolitan program in Situbondo Regency. The results of this study were expected to provide guidelines for the development of the Minapolitan program in Situbondo Regency. This study used a prospective analysis method. Method of minapolitan development strategy formulation used Analytical Hierarchy Process (AHP). This research produced scenarios that might occur in the future. These scenarios could serve as a guideline for the preparation of the minapolitan development strategy in Situbondo Regency. The results of the study showed that there were four scenarios will occur in the future, namely the optimistic developing scenario, the pessimistic developing scenario, there was still hope scenario and alert scenario. Based on discussions with experts, the most likely scenario to occur were an optimistic developing scenario and there was still hope scenario. Based on the scenarios that were most likely to occur, the strategy that can be applied for the development of Minapolitan in Situbondo Regency based on AHP method was to provide assistance and facilitate access to technology, markets, and capital.Keywords: analytical hierarchy process, minapolitan, prospective analysis